Fabrication of photoelectrode materials - Zhang, H.; Li, Xin Yong; Chen, G. (Springer New York, 2010)
In this chapter, a number of methods for the fabrication of film-structured photoelectrode materials were selectively reviewed. Sol-gel methods have long been employed for film fabrications. Direct assembly of particulate photocatalysts was also shortly discussed. The emphasis was placed on the development of photoelectrodes with enhanced photocatalytic performance due to either light absorption enhancement or increase in the separation of photogenerated charge carriers. Photocatalysts with enhanced light absorption were successfully developed by various doping techniques. And those with increase in charge carrier separations were made to have special crystalline structures such as nanorod/nanotubular arrays, interfacial region between coupled semiconductor components, and metal/semiconductor heterojunctions etc. Other structural characteristics such as high surface area and porosity were also achieved by various fabrication techniques as will be illustrated in this chapter. © 2010 Springer-Verlag New York.